An extreme sea level event along the northwest coast of the South China sea in 2011–2012. (15th May 2020) - Li, Juan; Tan, Wei; Chen, Meixiang; Luo, Fengyun; Liu, Yong; Fu, Qingjun; Li, Bingtian
Abstract: An extreme sea-level (ESL) event in 2011–2012 and its associated mechanisms are investigated using long-term tide gauge records and satellite altimeter data. The composite sea level anomaly (SLA) along the northwest coast of the SCS is up to 85.2 mm in 2012, reaching the highest since 1975. The ESL event in 2011–2012 is a combined effect of the mean sea-level rise, La Niña event and negative Pacific Decadal Oscillation (PDO) phase. The three factors work on different time scales. The long-term rising rate is 3.1 mm/yr from 1975 to 2015, the linear estimate of the mean sea level is 45.1 mm in 2012, accounting for about 52.9% of the total ESL (85.2 mm). After removing the linear trend, La Niña has a 28.2% contribution of the highest SLA, the negative PDO phase has a 51.3% contribution, and they jointly give rise to the ESL event on interannual to decadal time scales. The dynamic sea-level variation is the dominant contributor, explaining 72.8% of the observed sea-level differences between 2010 and 2012. The sea level pressure contributes 34.4%, and the steric effect contributes 7.7% of the observed results. Highlights: .The composite sea level anomaly is 85.2 mm in 2012 along the northwest coast of the SCS, reaching the highest since 1975. The extreme sea level event in 2011-2012 is a combined effect of the mean sea level rise, La Niña and negative PDO phase. The dynamic sea level is the dominant contributor, explaining 72.8% of the observed difference between 2010 and 2012.